2023
DOI: 10.3389/fimmu.2023.1142915
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of coated sodium butyrate improves growth performance of laying ducks by regulating intestinal health and immunological performance

Abstract: IntroductionThis study was conducted to assess the effects of dietary supplementation of coated sodium butyrate (CSB) on the growth performance, serum antioxidant, immune performance, and intestinal microbiota of laying ducks.MethodsA total of 120 48-week-old laying ducks were randomly divided into 2 treatment groups: the control group (group C fed a basal diet) and the CSB-treated group (group CSB fed the basal diet + 250 g/t of CSB). Each treatment consisted of 6 replicates, with 10 ducks per replicate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Our findings are in line with previous studies. Zeng et al (2023) , reported a slight reduction in ADFI in ducks with the addition of CSB, confirming our results. Additionally, Zhang et al (2022) , demonstrated that the inclusion of 800 mg/kg CSB in the feed significantly improved FCR, with no significant effect on ADFI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with previous studies. Zeng et al (2023) , reported a slight reduction in ADFI in ducks with the addition of CSB, confirming our results. Additionally, Zhang et al (2022) , demonstrated that the inclusion of 800 mg/kg CSB in the feed significantly improved FCR, with no significant effect on ADFI.…”
Section: Discussionsupporting
confidence: 91%
“…Research by Miao et al (2023 ), demonstrated that the addition of CSB to feed effectively increases the content of GSH-Px and T-AOC, while reducing MDA levels. Additionally, the research conducted by Zeng et al (2023) , also indicates that the addition of CSB can effectively enhance the serum antioxidant capacity of laying ducks. In line with these findings, our study revealed that the addition of CSB significantly increased the levels of SOD, CAT, and T-AOC in the serum of broiler chickens, providing compelling evidence for the beneficial effects of CSB in enhancing the serum antioxidant capacity of yellow-feathered broilers.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Li L. et al demonstrated that NaB ameliorates lipopolysaccharides-induced oxidative damage by upregulating the activities of antioxidative enzymes and reducing protein damage in MAC-T cells [31]. Additionally, the dietary supplementation of NaB can alleviate egg-laying stress in laying ducks by enhancing antioxidant ability [32]. The surplus of hepatic lipids can lead to alterations in cellular redox status, cumulating oxidative harm to biomacromolecules such as DNA, lipids, and proteins.…”
Section: Discussionmentioning
confidence: 99%